Case Report: Successful treatment of pityriasis rubra pilaris with deucravacitinib - Li, Yixuan; Guo, Meiliang; Sheng, Ziyao; Zhou, Zhehong; Liu, Na; Meng, Qinqin; Deng, Hui (Frontiers in Immunology, 2026)
Pityriasis rubra pilaris (PRP) is a rare inflammatory skin disease characterized by hyperkeratotic follicular papules, palmoplantar hyperkeratosis, and associated normal “islands of unaffected skin”. Its pathogenesis has not been fully elucidated, and treatment poses significant challenges. Conventional therapies include oral retinoids and topical emollients. In recent years, although biological agents have been used in treatment, they are associated with side effects such as an increased risk of infection, and some patients show no response to treatment, thus necessitating the exploration of new therapeutic approaches.This case represents the first reported use of a TYK2 inhibitor (deucravacitinib) for the treatment of PRP. The patient was a 39-year-old male who developed extensive erythema in December 2024. The erythema gradually increased and progressed to red punctate eruptions accompanied by mild desquamation, slight pruritus with a stinging sensation, and “islands of unaffected skin”. Initial treatment with topical dinoprostone and mometasone furoate cream was ineffective. In March 2025, the patient received deucravacitinib (6 mg daily) in combination with topical halometasone cream. At the 1-month follow-up, significant improvements were observed in erythema, desquamation, and pruritus. At the final 6-month follow-up, the skin lesions almost resolved, leaving only mild erythema and a small amount of desquamation. Both the disease severity and the patient’s quality of life were significantly improved. This case suggests that deucravacitinib exhibits favorable efficacy and safety in the treatment of PRP. However, due to the low incidence of PRP, which makes large-scale controlled trials difficult, and the lack of recognized treatment guidelines, more clinical studies are needed in the future to further verify the potential of deucravacitinib in the treatment of PRP.